Postnatal development of the endocrine pancreas of lactating guinea pigs (Cavia porcellus) - Rodríguez G., José (2012)
The postnatal development of the endocrine pancreas was studied in 45 guinea pigs of 1 to 15 days of age. The diameter of the Langerhans’s islets increased from 71.9 ± 13.2 μm at first day of age to 103.3 ± 32.5 μm at 15 days of age, showing a linear increase, but without statistical differences due to age. Similarly, the number of the β cells varied from 99.0 ± 29.7 at first day of age to 127 ± 29 cells at 15 days of age, and without significant differences due to age. The results shows that the endocrine pancreas development of lactating guinea pigs, determined by the diameter of the Langerhans’s islets and β cell number, tend to develop according to the age of the animals.